Swot Analysis of Tourism Development in Pematang Serai Village, Langkat Regency: Towards an Alternative Tourist Destination in North Sumatra - Manurung, Lambok; Widodo, Slamet (Sinergi International Journal of Management and Business, 2025)
This study aims to analyze tourism development strategies in Pematang Serai Village as an alternative tourist destination in Langkat Regency, North Sumatra, using a SWOT (Strengths, Weaknesses, Opportunities, Threats) approach. The independent variables in this study include Natural Potential, Community Involvement, and Infrastructure Support, while the dependent variable is Tourism Development. The number of respondents was 100 people, consisting of local residents, tourism actors, and visitors. The results of the study show that high natural potential, active community involvement, and growing infrastructure support are important factors in the development of alternative tourism. These findings contribute to the formulation of sustainable tourism development strategies in rural areas.